Lebanon : a history, 600-2011 - Harris, William W. (Studies in Middle Eastern history (New York, N.Y.), 2012)
In this impressive synthesis, William Harris narrates the history of the sectarian communities of Mount Lebanon and its vicinity. He offers a fresh perspective on the antecedents of modern multi-communal Lebanon, tracing the consolidation of Lebanon's Christian, Muslim, and Islamic derived sects from their origins between the sixth and eleventh centuries. The identities of Maronite Christians, Twelver Shia Muslims, and Druze, the mountain communities, developed alongside assertions of local chiefs under external powers from the Umayyads to the Ottomans. The chiefs began interacting in a common.